2017
DOI: 10.3346/jkms.2017.32.11.1828
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Fluid Status Using Bioimpedance Methods in Korean Pediatric Patients on Hemodialysis

Abstract: Adequate fluid management is an important therapeutic goal of dialysis. Recently, bioelectrical impedance methods have been used to determine body fluid status, but pediatric reports are rare. To determine the accuracy of bioelectrical impedance methods in the assessment of body fluid statusof children undergoing hemodialysis (HD), 12 children on HD were studied. A multi-frequency bioimpedance analysis device (Inbody S10) and bioimpedance spectroscopy device (BCM) were used to evaluate fluid status. Fluid remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…It has been revealed that BIA is a useful, easily applicable, and inexpensive tool for the evaluation of body composition of obese [10], cardiometabolic disorders [1][2][3][4], cancer [8], and hemodialysis patients [18]. Obtaining confidential information with regarding specific proportion of each section of body composition (TBW, FFM, %FM and FM) in health and also some disorder is a continue interest of clinical and scientist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been revealed that BIA is a useful, easily applicable, and inexpensive tool for the evaluation of body composition of obese [10], cardiometabolic disorders [1][2][3][4], cancer [8], and hemodialysis patients [18]. Obtaining confidential information with regarding specific proportion of each section of body composition (TBW, FFM, %FM and FM) in health and also some disorder is a continue interest of clinical and scientist.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, any impairment of nutritional conditions may have a remarkable effect on the content of body composition and trigger many serious clinical conditions [1,2]. The assessment of body composition has long been used to obtain important information with regard to health status of the individual [3,4]. Thus, the effective measurement of body composition becomes extremely important in clinical medicine.…”
Section: Introductionmentioning
confidence: 99%
“…To conduct the body composition analyses, an 8-electrode multifrequency bioelectrical impedance analyzer, the InBody S10 Biospace device (Biospace Co, Ltd, Seoul, Korea/Model JMW140), was used according to the manufacturer’s guidelines. 11 The patient was checked in lying position and the electrodes were attached in both ankles for legs and thumbs and middle fingers for arms during a free intake period before fasting by the same nutritionist. Body BCM, FM, FFM, and SM were obtained weekly using the InBody software from baseline until the end of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…In our current study, we adopted bioelectrical impedance as another index reflecting the severity of LLL. Bioimpedance measurement is a noninvasive technology that can accurately measure a patient's TBW, ECW, and intracellular body water in clinical settings [19,20]. Specifically, InBody is widely used for the diagnosis of lymphedema and monitoring limb edema [21,22].…”
Section: Reductionmentioning
confidence: 99%